Mammary cancer in man: experience of 20 cases - Lanza Barbieri, Mario; Priario, Julio C (Cirugía del Uruguay, 1977)
This type of cancer accounts for 1 % of malignant mammary tumors, in our country; 99 % correspond to women. It is a very rare disease and little is known about it. It appears later than in women and the patient also tends to see the doctor later than women do. Therapy and resources are the same for both sexes. This paper is based on a series of 20 such cancers